Imitating the Risky Decision-Making of Peers: An Experimental Study Among Emerging Adults. Issue 4 (August 2018) - Riedijk, Larisa; Harakeh, Zeena
This experiment examined whether emerging adults imitate the risky decision-making of peers and whether peer susceptibility functions as a moderator. Overall, 63 emerging adults participated with a confederate of the same gender. The participants were randomly assigned to the experimental (confederate engaged in risky decision-making) or control (confederate did not engage in risky decision-making) condition. Risky decision-making was measured with the Stop-Light Game task, and peer susceptibility was measured with a questionnaire. Linear regression analyses showed that the participants engaged in more risky decision-making when the peer displayed risky decision-making. Peer susceptibility was not found to be a significant moderator of this relationship. The findings showed that health education programs need to consider imitation to reduce the risky decision-making of emerging adults more effectively.